Working with the natural complexity: Selection and characterization of black cohosh root extract for use in toxicology testing. (February 2022) - Waidyanatha, Suramya; Cristy, Tim; Pierfelice, Jessica; Andre, Jon C.; Burback, Brian; Mutlu, Esra
Abstract: Black cohosh ( Actaea racemosa L.) is a botanical supplement marketed to women of all ages. Due to paucity of data to assess the safe use, the National Toxicology Program (NTP) is evaluating the toxicity of black cohosh. The use of an authentic, quality material is imperative to generate robust data. Because botanical materials are complex mixtures with variable composition, the selection of a material is challenging. We describe selection and phytochemical characterization of an unformulated black cohosh root extract (i.e., an extract that serves as source material for a formulated product) to be used in the NTP assessments . A material was selected using a combination of non-targeted and targeted chemical analyses, including confirmation of authenticity, absence of contaminants and adulterants, and similarity to a popular black cohosh product used by consumers. Thirty-nine constituents covering three major classes, triterpene glycosides, phenolic acids, and alkaloids were identified. Among constituents quantified, triterpene glycosides made up approximately 4.7% (w/w) with total constituents quantified making up 5.8% (w/w) of the extract. Non-targeted chemical analysis followed by chemometric analysis of various materials sold as black cohosh, and reference materials for black cohosh and other Actaea species further confirmed the suitability of the selected extract for use. Highlights: Despite use by women of all ages, safety data for black cohosh is limited. We present selection and characterization of an extract for safety testing. Non-targeted and targeted chemical analysis and chemometric analysis was used. Thirty-nine constituents covering three major classes of black cohosh were identified. Quantified constituents make up 5.8% of the total extract.